Corporate Sustainability, ESG, and the Triple Bottom Line: A Review of Key Challenges - Ch Das, Tilak; Bora, Prathana Kashyap; Das, Jyotisman (International Review of Management and Marketing, 2025)
The Triple Bottom Line (TBL) concept, introduced over two decades ago by John Elkington, was once seen as a breakthrough in redefining business success by including social and environmental responsibilities alongside profit. However, in recent years, even its creator has raised concerns about its practical impact and widespread misapplication. This study presents a systematic review of existing literature on the relationship between corporate sustainability and the TBL framework, with a particular focus on Environmental, Social, and Governance (ESG) criteria. Using stakeholder and agency theory as the conceptual lens, the paper explores how ESG integration has influenced corporate sustainability performance across different contexts. Following the PRISMA guidelines, the review process involved careful selection and screening of relevant studies from major databases. Bibliometric tools, including VOSviewer, were employed to visualize research trends, co-occurrence patterns, and thematic clusters. A total of 65 scholarly articles were analyzed, highlighting both the growing interest in sustainability discourse and the persistent challenges in translating TBL principles into measurable strategies. Key obstacles include inconsistent ESG frameworks, stakeholder conflicts, and difficulties in evaluation. The study contributes to the ongoing conversation by mapping critical research developments and identifying gaps that must be addressed to advance sustainable business practices.